2019
DOI: 10.16899/jcm.661279
|View full text |Cite
|
Sign up to set email alerts
|

The use of octreotide in the treatment of chylothorax

Abstract: The use of octreotide in the treatment of chylothorax Şilotoraksın tedavisinde oktreotidin kullanımı Chylothorax is defined as abnormal accumulation of lymphatic fluid in the pleural space. Chylothorax is a rare case and generally occurs after thoracic and cardiac procedures. Chylothorax causes respiratory and nutritional problems and a significant mortality rate. Good knowledge of the underlying pathophysiology enables early diagnosis and prevention of the chronic complications related to immunodeficiency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a separate study involving rutin treatment (benzo-γ-pyrone Dimorphandra mollis based bioflavonoid; 250mg or 500mg, per cat, q8h for 63 days), complete resolution was observed in a domestic cat (Kopko, 2005), and another study showed clinical improvement 3 out of 4 cats (Thompson et al, 1999). Recent findings have highlighted the efficacy of octreotide, which directly impacts lymphatic flow, in neoplastic and traumatic cases of chylothorax in humans (Esme, 2019). However, the response to octreotide treatment in cats with chylothorax varies.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study involving rutin treatment (benzo-γ-pyrone Dimorphandra mollis based bioflavonoid; 250mg or 500mg, per cat, q8h for 63 days), complete resolution was observed in a domestic cat (Kopko, 2005), and another study showed clinical improvement 3 out of 4 cats (Thompson et al, 1999). Recent findings have highlighted the efficacy of octreotide, which directly impacts lymphatic flow, in neoplastic and traumatic cases of chylothorax in humans (Esme, 2019). However, the response to octreotide treatment in cats with chylothorax varies.…”
Section: Introductionmentioning
confidence: 99%